2020
DOI: 10.1186/s12933-020-01163-9
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotection with SGLT2 inhibitors in type 2 diabetes over a spectrum of cardiovascular and renal risk

Abstract: Approximately half of all patients with type 2 diabetes (T2D) develop a certain degree of renal impairment. In many of them, chronic kidney disease (CKD) progresses over time, eventually leading to end-stage kidney disease (ESKD) requiring dialysis and conveying a substantially increased risk of cardiovascular morbidity and mortality. Even with widespread use of renin–angiotensin system blockers and tight glycemic control, a substantial residual risk of nephropathy progression remains. Recent cardiovascular ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 146 publications
(216 reference statements)
3
51
0
Order By: Relevance
“…Initially, the inhibitory effects of SGLT-2i can lead to tubule-glomerular negative feedback by enhancing natriuresis and sodium delivery to dense plaques, thereby reducing diabetic glomerular hyperfiltration caused by hyperglycaemia. SGLT-2i are thought to reduce chronic renal damage caused by hyperglycaemia [ 36 ]. The significant increase in haematocrit concentrations in patients receiving SGLT-2i appears to be associated with increased production of erythropoietin, which may also increase oxygen delivery to the kidneys and reduce renal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the inhibitory effects of SGLT-2i can lead to tubule-glomerular negative feedback by enhancing natriuresis and sodium delivery to dense plaques, thereby reducing diabetic glomerular hyperfiltration caused by hyperglycaemia. SGLT-2i are thought to reduce chronic renal damage caused by hyperglycaemia [ 36 ]. The significant increase in haematocrit concentrations in patients receiving SGLT-2i appears to be associated with increased production of erythropoietin, which may also increase oxygen delivery to the kidneys and reduce renal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Thus, SGLT2i have both cardioprotective and nephroprotective features. 7 , 8 , 10 This has been supported by the following EMPA‐REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients), DAPA‐HF (Dapaglifozin and Prevention of Adverse Outcomes in Heart Failure), and CANVAS (the CANagliflozin cardioVascular Assessment Study) trials. 5 , 6 , 11 , 12 , 13 , 14 , 15 Collectively, the results of the landmark trials demonstrated that SGLT2i correspond to a reduction in all cardiovascular mortality risks, reduced heart failure‐associated hospitalization, and decline in CKD progression in diabetic patients.…”
Section: Introductionmentioning
confidence: 87%
“…Another indirect action of SGLT2 inhibition is natriuresis; this further reduces blood pressure and slows down the progression of chronic kidney disease (CKD) 6 . Thus, SGLT2i have both cardioprotective and nephroprotective features 7,8,10 . This has been supported by the following EMPA‐REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients), DAPA‐HF (Dapaglifozin and Prevention of Adverse Outcomes in Heart Failure), and CANVAS (the CANagliflozin cardioVascular Assessment Study) trials 5,6,11–15 .…”
Section: Introductionmentioning
confidence: 96%
“…Up to 30% of the burden of CKD is a result of diabetes [ 3 ] and the progression to end stage renal failure in patients with diabetic kidney disease (DKD) is only slowed by current clinical therapies which attempt to target hyperglycemia and hypertension [ 4 ]. Sodium glucose cotransporter 2 (SGLT2) inhibitors are a new class of oral anti-hyperglycemic medications that are approved and indicated for type 2 diabetes and have shown promising renoprotective effects independent of their glucose lowering actions [ 5 ]. However, their use in type 1 diabetes is limited, mainly due to complications such as diabetic ketoacidosis as the main safety concern [ 6 ].…”
Section: Introductionmentioning
confidence: 99%